2020
DOI: 10.2147/prbm.s221435
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of Patients’ Perceptions of Physician–Patient Relational Empathy on an Inflammation Marker in Patients with Crohn’s Disease: The Intermediary Roles of Anxiety, Self-Efficacy, and Sleep Quality</p>

Abstract: Background: Physician-patient empathy is inextricably linked with outcomes of patients. The purpose of this study was to test whether anxiety, self-efficacy, and sleep quality played intermediary roles in relationships between patients' perceptions of physician-patient relational empathy and an inflammation marker in Crohn's disease patients. Methods: The study included 187 patients. At admission (T1) and 3 months after admission (T2), anxiety, self-efficacy, sleep, and the inflammatory marker IL6 of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…In line with the findings from a wealth of face-to-face studies ( 1 9 ), we found that doctors’ empathy as rated by the patients was consistently associated with less concern about symptoms and a perception of less severe symptoms after an online encounter. We also found that patients who rated their doctors as more empathic were more likely to report that their symptoms had alleviated.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In line with the findings from a wealth of face-to-face studies ( 1 9 ), we found that doctors’ empathy as rated by the patients was consistently associated with less concern about symptoms and a perception of less severe symptoms after an online encounter. We also found that patients who rated their doctors as more empathic were more likely to report that their symptoms had alleviated.…”
Section: Discussionsupporting
confidence: 88%
“…Empathy has an important role in doctor-patient encounters. A systematic review of studies published from 1995 to 2011 reported that medical doctors’ empathy supports patient satisfaction, psychological well-being, and better clinical outcomes (1), and later research has been in line with these results (2–9). However, contrasting findings also exist (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burnout is associated with a greater number of medical errors ( Shanafelt et al, 2010 ). Compassionate providers of care, on the other hand, elicit higher compliance with care, such as cancer screening, control of blood glucose in patients with diabetes, or inflammation and outcomes in patients with Crohn’s disease ( O’Malley et al, 2002 , 2004 , 2012 ; Hojat et al, 2011 ; Xu et al, 2020 ). Finally, compassion interventions, per se , may more directly affect disease, such as depression, anxiety, and pain ( Mongrain et al, 2018 ; Austin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“… 35 These findings are particularly relevant as physician-patient relational empathy has been shown to correlate with patient anxiety, sleep quality, and inflammatory markers. 36 Thus, more research is warranted to determine IBD patients’ perceived levels of support from medical staff and the resulting influence on disease outcomes. This may be particularly relevant in the adult IBD population, as access to social workers and child support workers dwindles upon transitioning from pediatric to adult clinics.…”
Section: Discussionmentioning
confidence: 99%